Heart rhythm-synchronized fibrin flap in a glaucoma tube shunt: The heartbeat acts as a drainage pump for the aqueous humor. Issue 27 (9th July 2021) - Tanabe, Hirotaka; Nakakura, Shunsuke; Tabuchi, Hitoshi
Abstract: Rationale: The amount of aqueous humor that is constantly produced by the ciliary processes and the equal amount that flows out through the trabecular meshwork via the drainage angle or through the uveoscleral route is very small (2–3 μg/min each), representing approximately 1% of the content of the anterior chamber; therefore, it is challenging to visualize its flow. Patient concerns: A 69-year-old man who had high intraocular pressure (IOP) (>20 mm Hg) with the maximum glaucoma eyedrop dose and presented with severe visual field loss (Humphrey Field Analyzer 30–2: –26.32 dB) had been implanted with a 350-mm 2 Baerveldt tube of the aqueous chamber type for refractory open-angle glaucoma. The IOP ultimately decreased (<15 mm Hg) with no need for glaucoma eyedrops. Diagnoses: After the procedures, a fibrin membrane repeatedly formed on the anterior surface of the intraocular lens. Interventions: This issue was resolved by two rounds of neodymium-doped yttrium aluminum granet (Nd:YAG) laser surgery and prescription steroidal eyedrops. Outcomes: During the laser surgery, an unusual and unintended fibrin flap appeared at the opening of the Baerveldt tube; this flap moved synchronously with the heartbeat, as verified by checking the pulse at the radial artery of the wrist. The fibrin flap mimicked the behavior of a cardiac valve, and the aqueous humor and stray fibrin particles mimicked the blood in the chambers of the heart. Although the Baerveldt tube itself is an artificial instrument that is not present in normal human eyes, we hypothesize that our observation shows the fundamental mechanism of aqueous humor drainage. Lessons: This novel, vividly descriptive observation highlights the important role of the heartbeat as a drainage pump in aqueous humor flow dynamics and IOP homeostasis, which are treatment targets for glaucoma, the leading cause of blindness. Abstract : Supplemental Digital Content is available in the text